Basic Life Support (BLS) Knowledge Level Evaluation Analysis of Non-Medical Employees Post Following BLS Training - Sulistiyorini Sulistiyorini; Budhi Setianto (Journal for Quality in Public Health, 2020)
In an effort to increase additional education programs to gain knowledge and skills in carrying out duties and functions, it can improve the performance of employees in the hospital. The phenomenon of the need for medical and non-medical personnel as personnel providing services in the hospital if you find emergency victims, both patients and hospital visitors, must understand the SOP for handling emergency patients. In addition, every medical service provider must have BLS capability. Patients are unconscious and do not see who is helping and where is the place, even patients are often not aware that the helper is not medical (non-medical), so the hospital requires medical and non-medical personnel to be able to do BLS. This type of research is descriptive quantitative. The purpose of this study is to provide an overview of the characteristics of non-medical employees, whether there is a relationship with knowledge based on the training that has been followed. The research sample is that all non-medical employees who have attended BLS training at RSI Surabaya A.Yani are 33 people. Characteristics of respondents at the Surabaya Islamic Hospital with the age category> 45 years 39.4%, the majority are male 51.5%, the latest education is a bachelor's degree 51.5%, the status of permanent employees is 81.8%, the majority is married marital status 82 %, working period 16-25 years 33.3%. The conclusion of this study is that the knowledge of non-medical employees at the Surabaya Islamic Hospital is declared good because by participating in the training, they can gain knowledge and skills in performing first aid actions for victims.